Species Identification and Strain Differentiation of Dermatophyte by (GACA)4-Primer based PCR - Al-Hashemi, Asra; Al- Jibouri, Mona; Ghali, Zafir; Kdhim, Bara’a (Iraqi Journal of Science, 2023)
Dermatophytes are a group of morphologically and physiologically related molds some of which cause well defined infections: dermatophytoses (tineas or ringworm). The present study aims at identification of dermatophytes species and varieties from patients in Wasit province-Iraq using molecular approach based PCR fingerprint.The short oligonucleotide (GACA)4 is a microsatellite primer was used in this study for identification of dermatophyte isolates. The results identified different species and varieties among dermatophytes. The numbers of resulting PCR bands ranged from 1 to 4 (size range, 600bp to 1600bp) for each species. The resulting patterns were distinct for Trichophyton and Microsporum species and varieties.Trichophyton soudanense and Trichophyton verrucosum revealed distinguishable profiles with four largest bands (800bp to 1900bp) among Trichophyton species. (GACA)4 is able to amplify all species of Microsporum producing intraspecies variation which is observed with Microsporum canis (rough strain) and Microsporum canis (smooth strain), all of which had different band pattern. We conclude that (GACA)4-based PCR has utility as a rapid method for identification of dermatophytes species as well as its utility for differentiation of Trichophyton and Microspmoru species and varieties.